2022
DOI: 10.1017/jfm.2022.776
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between upstream-propagating guided jet waves and shear-layer instability waves near the nozzle of subsonic and nearly ideally expanded supersonic free jets with laminar boundary layers

Abstract: The interactions between upstream-propagating guided jet waves and shear-layer instability waves near the nozzle of subsonic and nearly ideally expanded supersonic, isothermal free jets are investigated for jets at Mach numbers between 0.50 and 2 with fully laminar exit boundary layers of different thicknesses. The velocity spectra in the shear layers downstream of the nozzle exhibit strong narrow peaks for the first azimuthal modes, associated with growing Kelvin–Helmholtz instability waves. The frequencies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 80 publications
5
38
0
Order By: Relevance
“…Here is the non-dimensional frequency in terms of Strouhal number scaled with the exit momentum thickness of the nozzle boundary layer. This is consistent with the dominant shear layer spectrum for the thin boundary layer of a Mach circular jet, reported by Bogey (2022). On both planes, the peak N factor decreases with increasing frequencies.…”
Section: Linear Response Of the Flowsupporting
confidence: 92%
See 1 more Smart Citation
“…Here is the non-dimensional frequency in terms of Strouhal number scaled with the exit momentum thickness of the nozzle boundary layer. This is consistent with the dominant shear layer spectrum for the thin boundary layer of a Mach circular jet, reported by Bogey (2022). On both planes, the peak N factor decreases with increasing frequencies.…”
Section: Linear Response Of the Flowsupporting
confidence: 92%
“…Here St θ is the non-dimensional frequency, Strouhal number, based on the momentum thickness at the nozzle exit, θ. Recent studies by Bogey (2022) have also shown that for an axisymmetric nozzle with laminar exit conditions, the most amplified instability varies with Mach number between St θ = 0.018 for M = 0.5 to St θ = 0.0025 for M = 2.0. The azimuthal mode of the instability was also observed to be sensitive to the jet Mach number.…”
Section: Introductionmentioning
confidence: 93%
“…For the free jets, in figures 11(d)-11( f ), several high-energy spots are found around specific frequencies. They result from the coupling between the free-stream upstream-propagating GJWs and the shear-layer instability waves near the nozzle, as shown by Bogey (2022a) for free jets with fully laminar exit boundary layers. For a thicker boundary layer, they are located farther downstream, due to the reduction of the peak instability growth rate.…”
Section: Amplification and Gain In Amplitude Of The Axisymmetric Aero...mentioning
confidence: 96%
“…The spectra of the radial velocity fluctuations of aerodynamic nature obtained for the three impinging jets and the corresponding free jets (Bogey 2022a) for n θ = 0 at r = r 0 are For the impinging jets, the frequencies of the jet initial most-amplified instability waves obtained at z = 0.1r 0 for n θ = 0 using LSA, half of these frequencies, and the frequencies of the small peaks found in the near-nozzle spectra for M06BL10 and M06BL20, are also depicted. For the free jets, in figures 20(d)-20( f ), the highest levels are found in two spots centred, e.g.…”
Section: Velocity Spectramentioning
confidence: 99%
See 1 more Smart Citation